Impact of L38↑N↑L insertions on structure and function of HIV-1 South African subtype C Protease - Maputsoe, Xolisiwe (My University, 2012)
The Human Immunodeficiency Virus (HIV) subtype C accounts for the majority of infections in Southern Africa. The HIV protease is one of the targets in HIV treatment due to its pivotal role in HIV maturation in the host cell. However, because of polymorphisms in the HIV genome, drug resistance becomes a major problem in HIV treatment. Polymorphisms in the HIV protease gene result in altered substrate cavities, and /or flap hinge modifications leading to unfavourable drug interaction with the enzyme. The most common form of drug resistant mutations is single amino acid substitutions. Although, amino acid insertions have been reported, this form of mutation in the HIV protease is rare. L38↑N↑L insertion is a unique form of HIV protease polymorphism that was isolated from a patient failing drug therapy in South Africa. The objective of this research was to assess the impact of the L38↑N↑L insertions, with accompanying background mutations, on the structure and function of this form of polymorphism in HIV-1 South African subtype C protease. The far-UV circular dichroism (CD) spectra of L38↑N↑L protease shows a trough at 203 nm, suggesting alterations in the secondary structure content of this mutant. Whereas the wild type (WTCSA-HIVPR) displays a trough at 215 nm. However, tertiary structure characterisation using fluorescence spectroscopy did not detect changes within the local tryptophan environment of L38↑N↑L protease in comparison with the wild type due to no significant shift in emission wavelength. The specific activity of L38↑N↑L protease and wild type was 28.0±1.3 μmol.min-1.mg-1 and 123.45±6.4 μmol.min-1.mg-1 respectively. The turn-over number for L38↑N↑L protease and wild type was 1.0 × 10-3 ± 6.0 × 10-5 and 7.7 × 10-3 ± 5.6 × 10-4 respectively. As much as the presence of known drug resistance mutations in L38↑N↑L can be attributed to drug resistance, it should also be noted that the insertions may have also caused local structural alterations that may have enhance drug resistance of L38↑N↑L. These changes could have lead to the decreased catalytic activity of the L38↑N↑L protease. Homology modelling studies show that the insertions in L38↑N↑L protease may have resulted in a fold similar to 2HS1 (PDB code), which has a modification on the flap hinge. In addition, the homology modelling studies suggest that L38↑N↑L protease may have a second inhibitor binding site next to one of the flap hinge regions as seen in the 2HS1 model. In conclusion, the L38↑N↑L insertions and accompanying background mutations may have contributed to the local structural modifications that lead to drug resistance in L38↑N↑L protease.
Keywords: HIV (viruses); Proteolytic enzymes.